The formation of psicoeducative orientation competence in dentistry students - Soledad Y. García Peláez; Silvia Colunga Santos; Mayelin Soler Herrera (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
A developed research with qualitive approach was carried out in Dentistry faculty in the Medical College during the period of September 2016 to July 2018. A universe of 145, 4th- course Dentistry students and a sample of 70 students (class A) who reported 48.27 % were selected. From this study on, an insufficient treatment to emotional affections in children and teenagers with dentomaxillofacial anomalies was proved to limit the professional performance in dentistry students. So, the effectiveness of a pedagogical intervention program to educate the psicoeducative orientation competence to children and teenagers was assessed. The proposal is structured in three phases devoted to diagnosis-motivation, planification-action and evaluation. It was corroborated the effectiveness of the intervention program through critical opinion and collective construction workshop in order to favorite psicoeducative orientation in these age groups.